Epidemiological features and risk factors for measles and rubella in Taiwan during 2011 to 2020. Issue 43 (28th October 2022) - Yu, Chia-Peng; Chen, Bao-Chung; Chou, Yu-Ching; Hsieh, Chi-Jeng; Lin, Fu-Huang
Abstract : The risk of geographic transmission of infectious diseases due to air travel varies greatly. Our aim is to survey empirical data that provide a retrospective historical perspective on measles and rubella. This study used the open data website provided by the Taiwan Centers for Disease Control (TCDC) to extract the reported numbers of measles and rubella case between 2011 and 2020. There were 306 cases of measles and 135 cases of rubella. The incidence of measles and rubella per million population were 0 to 6.0 and 0 to 2.6, respectively. There was a gradual increase in the numbers of cases in those aged 20–39 years, and distinct duration patterns. It indicated that the risk of contracting rubella has significantly decreased in the last 5 years. Measles cases aged 20 to 39 years accounted for 72.5% of all cases. Rubella cases aged 20 to 39 years accounted for 59.3% of all cases. The male and residency in the Taipei metropolitan area or northern area were identified as potential risk factors for measles and rubella. Coverage with the first dose of the measles, mumps and rubella (MMR) vaccine in Taiwan increased from 97.31% to 98.86%, and the uptake rate of the second dose of the MMR vaccine increased from 95.73% to 98.39% between 2010 and 2020. Furthermore, the numbers of imported cases of measles (n = 0) and rubella (n = 0) reported during the coronavirus disease 2019 (COVID-19) pandemic were lower than those from 2011 to 2019. Measles and rubella cases were imported most frequently from Cambodia and Vietnam. This study represents the first report of confirmed cases of acquired measles and rubella from surveillance data of the TCDC between 2011 and 2020, also demonstrates that the numbers of cases of measles and rubella significantly decreased in Taiwan during the COVID-19 pandemic.